Shear strengthening of hybrid externally-bonded mechanically-fastened concrete beams using short CFRP strips: Experiments and theoretical evaluation. (15th December 2019) - Hadhood, Abdeldayem; Agamy, Mohamed H.; Abdelsalam, Moataz M.; Mohamed, Hamdy M.; Aly El-Sayed, Tarek
Highlights: Behavior of externally-bonded (EB) mechanically-fastened (MF) RC members. Optimized-size of composite CFRP strips for shear. Shear strength of externally-bonded mechanically-fastened RC members. Effect of test parameters on shear strength of EB/MF-RC members. Design recommendations for EB/MF-RC RC members. Abstract: Hybrid externally bonded (EB) mechanically-fastened (MF) technique for carbon-fiber-reinforced-polymers (CFRP) strips offers a high potential in shear strengthening to preclude debonding phenomenon and effectively utilize the maximum use of CFRP. This study investigated the failure envelope of reinforced concrete (RC) beams, designed deficient in shear, strengthened with hybrid EB/MF technique and reduced-size CFRP strips. The investigated parameters included strip length, number, spacing, and diameter of fasteners. The beams were subjected to three-point loaded testing with a shear span-to-depth ratio of 2.5. The strengthening had an axial rigidity of 1.8 GPa. The hybrid EB/MF technique for the reduced-size CFRP strips (up to 44% length reduction) inhibited crack propagation and could preclude the debonding phenomenon provided that adequate spacings of fasteners used. The results showed that the hybrid EB/MF specimens with reduced-size CFRP strips could achieve up to 65% shear load gain over the unstrengthened specimen. Also, a theoretical evaluation was conducted using other specimens from past studies to estimate the contribution of CFRP strips with and without steel stirrups. In addition, the ultimate shear loads were predicted, as per North-America's guidelines, and compared with the experimental results. Finally, a set of recommendations was drawn based on the results of this study and the available literature.